KONTRASTIVITAS DIATESIS PASIF BAHASA INDONESIA DAN BAHASA JEPANG DALAM DONGENG JEPANG MOMOTARÅŒ - Sukma Luh Putu Ratnayanti; Setiawan Luh Gde Intan Purnama Sari (Universitas Warmadewa, 2020)
This study aims at (1) describing the rules of the passive voice in Indonesian and Japanese languages, (2) finding the markers of passive sentences in Indonesian and Japanese languages, (3) describing the similarities and differences of passive sentences in Indonesian and Japanese. The data is collected by the descriptive method. The method of data analysis is a contrastive analysis. The result of data analysis is presented by method Indonesian passivization explained by the change of morphology on the verb, for example, Indonesian language passive using markers di-, ter- and ke-an. Meanwhile, Japanese language passivization is described by verbs and nouns functioning as objects in passive sentences. Japanese verbs consist of consonant verbs, vowel verbs, and irregular verbs. Passive sentences in the Japanese language are marked by marker ni + V-areru for consonant verbs, markers ni + V-areru for vocal verbs, ni + V-areru for irregular verbs, and ni + yotte V-areru/V-rareru for verbs that are followed as object inanimate nouns. Similarly, there are two passivizations in Japanese: passivization using the direct object and the indirect object. However, the indirect passivization of the Japanese can use transitive verbs or intransitive verbs. Japanese passive sentences express the completion of an action and an unpleasant meaning. In comparison, the Japanese passive sentence is not used as regularly as Indonesian passive because Japanese passive tends to express a point of view first person. In addition, another difference between passive sentences in Indonesian and Japanese is that in Japanese it is important to know the subject.